Can the European low-cost airline boom continue?: Implications for regional airports - Nigel Peter Stewart Dennis (European Regional Science Association (ERSA), 2004)
At a time when the traditional major airlines have struggled to remain viable, the low-cost carriers have become the major success story of the European airline industry. This paper looks behind the headlines to show that although low-cost airlines have achieved much, they too have potential weaknesses and face a number of challenges in the years ahead. The secondary and regional airports that have benefited from low-cost carrier expansion are shown to be vulnerable to future changes in airline economics, government policy and patterns of air service. An analysis of routes from London demonstrates that the low-cost airlines have been more successful in some markets than others. To attractive and historically under-served leisure destinations in Southern Europe they have stimulated dramatic growth and achieved a dominant position. To major hub cities however they typically remain marginal players and to secondary points in Northern Europe their traffic has been largely diverted from existing operators. There is also evidence that the UK market is becoming saturated and new low-cost services are poaching traffic from other low-cost routes. Passenger compensation legislation and possible environmental taxes will hit the low-cost airline industry disproportionately hard. The high elasticities of demand to price in certain markets that these airlines have exploited will operate in reverse. One of the major elements of the low-cost business model involves the use of smaller uncongested airports. These offer faster turn-arounds and lower airport charges. In many cases, local and regional government has been willing to subsidise expansion of air services to assist with economic development or tourism objectives. However, recent court cases against Ryanair now threaten these financial arrangements. The paper also examines the catchment areas for airports with low-cost service. It is shown that as well as stimulating local demand, much traffic is captured from larger markets nearby through the differential in fare levels. This has implications for surface transport, as access to these regional airports often involves long journeys by private car. Consideration is then given to the feasibility of low-cost airlines expanding into the long-haul market or to regional operations with small aircraft. Many of the cost advantages are more muted on intercontinental services – for example, aircraft utilisation is already high and few routes have sufficient local demand without the use of hubbing. Large turbo-prop aircraft such as the DHC Dash 8 400 series offer very good economics compared to regional jets on short to medium sectors where demand is too thin to support a Boeing 737 operation. flybe is using these on certain `third level' routes in Britain and other opportunities are identified in mainland Europe. It is concluded that there are still good growth prospects for low-cost airlines in Europe, especially in France, Italy and some of the new EU member states but rather than growing to dominate the air transport industry, an equilibrium position is likely to be reached. Some regional airports may see their services reduce once the market becomes saturated or the relative competitive position of the major airports and airlines improves.
Keywords: 330